Liar Paradox and the Rhetoric of Group Self-Deprecation - Talanker, Sergei (Logic and Logical Philosophy, 2026)
What does a Cretan mean when he says that all Cretans are liars? What is his intention? While formal logic only relates to the truth values of the Liar paradox, we relate to its normative and social aspects. We argue that such utterances are used to imply that certain behaviors, even if despicable, constitute local norms. One may posit such claims either to point out that he has transcended the local culture, to socialize others into local customs, or to deflect from being caught lying. This paradox exemplifies group self-deprecation, a communicative practice intended to get us to disagree, rather than agree, with the disparaging claim and blunt the negative consequences of poor behavior. Its rhetoric relies upon tu quoque, secundum quid and naturalistic fallacies.